1995
DOI: 10.1159/000139284
|View full text |Cite
|
Sign up to set email alerts
|

Antiestrogenic Properties of Raloxifene

Abstract: This 21-day, open-label study evaluated the effects of raloxifene and tamoxifen on estrogen-induced changes in serum levels of anterior pituitary hormones (prolactin, luteinizing hormone, and follicle-stimulating hormone), sex steroids (testosterone, estradiol), and binding globulins [thyroid binding globulin (T3 resin uptake), transcortin, sex steroid binding globulin]. Seventeen healthy male volunteers completed the study after being randomized to one of three treatments: raloxifene, tamoxifen, or placebo. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Data about the action of raloxifene on human pituitary secretion are, at present, few. In male volunteers the drug blunts estrogeninduced changes in serum gonadotropin levels (8). In premenopausal women, Baker et al (9) showed that raloxifene increases serum FSH and E2 levels, and reduces PRL concentrations by 10 -35% of basal values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data about the action of raloxifene on human pituitary secretion are, at present, few. In male volunteers the drug blunts estrogeninduced changes in serum gonadotropin levels (8). In premenopausal women, Baker et al (9) showed that raloxifene increases serum FSH and E2 levels, and reduces PRL concentrations by 10 -35% of basal values.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although some studies, performed in vitro or in rats, show that raloxifene acts as a pure estrogen antagonist at the pituitary level (5,6), others show that it exerts an estrogenic action on the hypothalamic -pituitary structures (7). In male volunteers, raloxifene blunts estrogen-induced changes in serum anterior pituitary hormone levels (8), whereas in premenopausal women, it does not alter the length of the menstrual cycle or the day of luteinizing hormone (LH) surge, but stimulates follicle-stimulating hormone (FSH) secretion, increases serum 17b-estradiol (E2) levels and decreases serum prolactin (PRL) values (9). In postmenopausal women, the effect of raloxifene on pituitary function has been little investigated, even though this drug is currently approved for the prevention of postmenopausal osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens 22,407,408 Ovulation suppressants and anticancer Heroin and methadone 409 Opiates (in addicts) Clofibrate 410 Hypolipidemic 5-Fluorouracil 411 Anticancer Perphenazine 412 Tranquilizer Tamoxifen 413,414 Chemotherapy Raloxifene [414][415][416] Osteoporosis…”
Section: Increase Tbg Concentrationmentioning
confidence: 99%
“…HCl, [176] was developed to maintain the beneficial estrogenic activity on bone and lipids, while mimicking antiestrogenic activity on endometrial and breast tissues [179]. The initial use of raloxifene as a breast cancer drug [180] was aborted due to its poor performance in comparison to tamoxifen in laboratory model. However, it is being widely considered as a prophylactic therapy in the prevention of breast cancer in high-risk women [77].…”
Section: Raloxifenementioning
confidence: 99%